Is It Truly Household Income Affect Underweightin Children Under Five Years Old ? Evidence From Indonesia: Underweightin Children - La Djabo Buton; Fitri Rachmillah Fadmi (STIKes Mandala Waluya Kendari, 2023)
Background: Underweight is a nutritional problem that still often occurs in children under five in Indonesia and abroad. Indonesia is a maritime country, where most of the territory is water so that the population living in coastal areas is not small. Many factors influence the occurrence of under-nutrition under five in coastal areas. Toddlers who experience underweight will experience physical growth disorders, morbidity and even risk of death. The purpose of this study was to determine the dominant factor in the incidence of underweight in children under five in the coastal area. Methods: This type of research is analytic observational with a cross sectional study design. The population in this study were mothers who had toddlers aged 12 – 59 months with a total sample of 68 toddlers who were selected using simple random sampling technique. Data was collected by interview method using a questionnaire and then analyzed using chi-square test and logistic regression. Results: This study found that household income was the main factor for underweight in children under five years of age, although there were many other contributing factors such as mother's knowledge, parenting style, history of infectious diseases. Conclusions: Low income causes the purchasing power of food to be low, causing family food consumption to decrease which ultimately affects the weight of children under five. For this reason, the role of mothers, families and the government is needed in reducing the prevalence of underweight in toddlers in the coastal area, Indonesia.